New Approaches to Ilkhanid History
1 online resource.
Keywords: As the title implies, New Approaches to Ilkhanid History explores new methodologies and avenues of research for the Mongol state in the Middle East. Although the majority of the Ilkhanate was situated in Iran, this volume considers other regions within the state and moves away from focusing on the center and the Ilkhanid court. New consideration is given to the source material, particularly how they have been composed, but also how the sources can inform on the provinces of the Ilkhanate. Several authors also examine lower-tier personages, groups, and institutions.